Changes in sensory proteins in the bladder urothelium of patients with chronic kidney disease and end‐stage renal disease. Issue 2 (9th September 2018) - Chen, Sheng‐Fu; Lee, Cheng‐Ling; Kuo, Hann‐Chorng
Abstract : Objective: Patients with chronic kidney disease (CKD) or end‐stage renal disease (ESRD) frequently have lower urinary tract symptoms, such as frequency, urgency, or bladder pain. This study evaluated sensory protein expression in the bladder urothelium of patients with CKD or ESRD. Methods: Twenty‐seven patients with ESRD or CKD and urodynamically proven detrusor underactivity (DU; n = 8) or bladder oversensitivity (n = 19) were enrolled in the study. These patients, and 10 controls, underwent cystoscopic biopsies of the urothelium. Western blotting analysis was used to examine the expression of sensory proteins, namely purinergic P2X3, muscarinic M2 and M3, and β3 ‐adrenergic (AR) receptors, as well as inducible (i) and epithelial (e) nitric oxide synthase (NOS), in tissue samples. Expression was compared between CKD or ESRD patients and controls. Results: P2X3 receptor expression was lower, whereas β3 ‐AR was expression higher in the bladder urothelium of the patient group (ESRD and CKD combined) compared with controls. In addition, compared with controls, CKD patients had significantly lower P2X3 receptor expression, whereas ESRD patients had significantly higher M3 receptor expression. There were no significant differences in M2 receptor, eNOS, and iNOS expression between ESRD or CKD patients and controls. Patients with DU had significantly higher M2 and M3 receptor expression. There were no significant differences in the expression of any protein between ESRD and CKD patients, regardless of the presence of bladder pain or anuria. Conclusion: Significantly decreased P2X3 receptor and increased β3 ‐AR expression are seen in the bladder urothelium of patients with ESRD or CKD. The expression of these sensory proteins is not associated with decreased bladder capacity or anuria status in patients with ESRD or CKD.